Constructing Methodology for Qualitative Research Researching Education and Social Practices - Harreveld, Bobby; Danaher, Mike; Lawson, Celeste; Knight, Bruce Allen; Busch, Gillian (Palgrave Studies in Education Research Methods,, 2016)
This book explores the webs of vulnerability in methodological decision-making that illustrate the deceptive strength of qualitative research. Each chapter will resonate with readers differently as they read themselves into the tensions and tangles of qualitative research when confronted with the challenges of estabilishing methodological frameworks for educational and social enquiry. The authors are postgraduate, early career researchers and supervisors who analyse their methodological encounters with the nimble, fluid, messy and iterative processes of qualitative research. The book flows structurally from positioning the researcher within these processes to the manoeuvring of self across necessarily selective social science disciplines in education, arts and humanities. It rejuvenates the pioneering spirit, the sense of mission and innovativeness of qualitative research. Bobby Harreveld is Professor of Education and Deputy Dean (Research) in the School of Education & the Arts at Central Queensland University, Australia. She works in postgraduate early career researcher education, learning transitions and professional education pathways. She is co-author of Deschooling L'earning: Young Adults and the New Spirit of Capitalism. Mike Danaher is Senior Lecturer of History and Geography at Central Queensland University, Australia. He has published in the fields of environmental and geographical education. He is co-author of Researching Education with Marginalized Communities. Bruce Allen Knight is Professor of Education at Central Queensland University, Australia. He has more than 200 publications and worked on large research projects worth more than AUD$5 million from such granting bodies as the Australian Research Council. Celeste Lawson is Lecturer and Head of the Professional Communication Program at Central Queensland University, Australia. Her research interests include policing, police culture, organisational communication and social media in an organisational context. Gillian Busch is Senior Lecturer in Education at Central Queensland University, Australia. Gillian has methodological expertise in qualitative approaches including ethnomethodology and conversation analysis.